Integrating Cash Waqf Linked Sukuk (CWLS) and Corporate Waqf Schemes Model for Productive Financing: An Islamic Economic Analysis - M Said, Muhammad; Amalia Tursina, Anisya; Fitri, Yessi; Fatchurohman, Nanang (Islamic Banking and Finance Review, 2026)
Cash waqf has gained increasing attention as a strategic instrument in Islamic social finance, supporting sustainable development and community empowerment. In Indonesia, the emergence of Cash Waqf Linked Sukuk (CWLS) represents an innovative mechanism that integrates waqf funds with government Sukuk to finance social programs. However, its effectiveness remains constrained by low Islamic financial literacy, limited participation by retail investors, and weak managerial capacity among Nazhir institutions. This study proposes a hybrid institutional model that combines CWLS as a government-backed fund-raising instrument with Corporate Waqf entities as professional fund managers. Using a descriptive qualitative approach based on library research, the study analyzes academic literature, regulatory frameworks, and institutional reports (2020–2025). Evidence from CWLS Series SWR001 and SWR003 indicates growing public participation and funding for healthcare and social programs. The findings suggest that the proposed hybrid model can enhance accountability, strengthen social impact, and increase public trust. This study contributes to the development of an inclusive and sustainable Islamic social finance system aligned with the objectives of Maqasid al-Sharia.